Clash of the titans: interferons and SARS-CoV-2. Issue 12 (December 2021) - Jouvenet, Nolwenn; Goujon, Caroline; Banerjee, Arinjay
Abstract : Interferons are our first line of defense against invading viruses. However, viruses encode effector proteins that can modulate human interferon responses. In this forum article, we highlight important discoveries and discuss outstanding questions that will enable us to better understand the nuances of this evolutionary battle between interferons and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).